Ragam Jenis Nyamuk di Sekitar Kandang Babi dan Kaitannya dalam Penyebaran Japanese Encephalitis - Hadi, Upik Kesumawati; Soviana, Susi; Syafriati, Tatty (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
The mosquitoes species in pig pen area and its relation to the trasmission of Japanese Encephalitis(JE) in North Sumatra Province was studied as the first step of the investigation on JE prevalence inIndonesia. The aim of this research is to determined the mosquitoes species that can be a potential vectorsof JE and its relation to the prevalence of JE reactor of pigs in North Sumatra. Mosquito collections werecarried out by using ultra violete light trap, Magoon trap and human landing collections. Serological studywas done by using competitive enzyme linked-immunosorbent assay (C-ELISA) methode. The resultsshowed several mosquitoes species i.e. Culex tritaeniorhynchus, Cx. quinquefasciatus, and Cx. fuscocephalusthat can be a potential vectors of JE was found in this province. The environmental conditions and the pigfarm and horses stable management supported the development of ideal breeding places for mosquitoesand other blood sucking flies. It was reported also that the prevalence of JE reactors in pig farms and horsestable in North Sumatra was high (71.67%). The high prevalence of JE reactors indicated that the infectionof JE was actively occured between pigs-mosquitoes-pigs in thise area.
Keywords: Mosquitoes, pig, Japanese encephalitis, North Sumatera